Piers, jetties and related structures exposed to waves : guidelines for hydraulic loadings - Cuomo, Giovanni; Polidoro, Andrea; Allsop, William (Emerald Publishing Limited, 2024)
Piers, Jetties and Related Structures Exposed to Waves, Second Edition delivers guidelines for engineers to analyse and optimise pier and jetty designs. With ports now having to account for larger ship sizes, there is an increasing need for these marine structures to be longer and constructed in significantly deeper water. Increased construction costs, structures in exposed locations, and health and safety concerns are just some of the aspects that a coastal engineer must consider when designing and building new maritime structures. This fully revised and updated edition provides full descriptions of the process covering: guidance on hydraulic design, including design wave conditions, prediction of scour and vessel mooring loads; new methods (developed from extensive laboratory testing) for the prediction of wave loading, including forces on the underside of jetty decks; new equations, graphs and coefficients for wave loadings; updated coefficients for impulsive loads; revised discussion on effects of trapped air expanded discussion on scaling loads from hydraulic models. With a vastly experienced team with associations to HR Wallingford, Piers, Jetties and Related Structures Exposed to Waves is the essential reading for maritime designers and consultants tasked with analysing, designing and constructing piers and jetties.
Includes index.
Keywords: Piers -- Design and construction.; Technology & Engineering -- Civil -- General.; Maritime and nautical trades.; Civil engineering, surveying and building.; elektronické knihy; electronic books